Outcome after liver resection for primary and recurrent intrahepatic cholangiocarcinoma. Issue 6 (10th September 2019) - Nickkholgh, A.; Ghamarnejad, O.; Khajeh, E.; Tinoush, P.; Bruckner, T.; Kulu, Y.; Mieth, M.; Goeppert, B.; Roessler, S.; Weiss, K. H.; Hoffmann, K.; Büchler, M. W.; et al.
Abstract : Background: Liver resection is the only curative therapeutic option for intrahepatic cholangiocarcinoma (ICC), but the approach to recurrent ICC is controversial. This study analysed the outcome of liver resection in patients with recurrent ICC. Methods: Demographic, radiological, clinical, operative, surgical pathological and follow‐up data for all patients with a final surgical pathological diagnosis of ICC treated in a tertiary referral centre between 2001 and 2015 were collected retrospectively and analysed. Results: A total of 190 patients had liver resection for primary ICC. The 1‐, 3‐ and 5‐year overall survival (OS) rates were 74·8, 56·6 and 37·9 per cent respectively. Independent determinants of OS were age 65 years or above (hazard ratio (HR) 2·18, 95 per cent c.i. 1·18 to 4·0; P  = 0·012), median tumour diameter 5 cm or greater (HR 2·87, 1·37 to 6·00; P  = 0·005), preoperative biliary drainage (HR 2·65, 1·13 to 6·20; P  = 0·025) and local R1–2 status (HR 1·90, 1·02 to 3·53; P  = 0·043). Recurrence was documented in 87 patients (45·8 per cent). The mean(s.d.) survival time after recurrence was 16(17) months. Independent determinants of recurrence were median tumour diameter 5 cm or more (HR 1·71, 1·09 to 2·68; P  = 0·020), high‐grade (G3–4) tumour (HR 1·63, 1·04 to 2·55; P  = 0·034) and local R1 status (HR 1·70, 1·09 to 2·65; P  = 0·020). Repeat resection with curative intent was performed in 25 patients for recurrent ICC, achieving a mean survival of 25 (95 per cent c.i. 16 to 34) months after the diagnosis of recurrence. Patients deemed to have unresectable disease after recurrence received chemotherapy or chemoradiotherapy alone, and had significantly poorer survival. Conclusion: Patients with recurrent ICC may benefit from repeat surgical resection. Abstract : The outcomes of liver resection in patients with intrahepatic cholangiocarcinoma in a tertiary referral centre were evaluated. Patients with recurrent intrahepatic cholangiocarcinoma may benefit from repeat surgery with curative intent. Surgery for recurrent iCCA may be beneficial. Abstract : Antecedentes: La resección hepática es la única opción terapéutica curativa para el colangiocarcinoma intrahepático ( intrahepatic colangiocarcinoma, iCCA), pero el enfoque terapéutico de la recidiva del iCCA es controvertido. En este estudio se analizaron los resultados de la resección hepática en pacientes con recidiva de un iCCA. Métodos: Se recopilaron de forma retrospectiva y se analizaron los datos demográficos, radiológicos, clínicos, quirúrgicos, de anatomía patológica y de seguimiento de todos los pacientes con diagnóstico anatomopatológico definitivo de iCCA en un centro de referencia terciario entre 2001 y 2015. Resultados: En total, 190 pacientes se sometieron a resección hepática por iCCA primario. La supervivencia global ( overall survival, OS) a 1, 3 y 5 años fue del 75%, 57% y 38%, respectivamente. La edad de ≥ 65 años (cociente de riesgos instantáneos, hazard ratio, HR 2, 2, i.c. del 95% 1, 2‐4, 0, P = 0, 012), la mediana del diámetro del tumor ≥ 5 cm (HR 2, 9, i.c. del 95% 1, 4‐6, 0, P = 0, 005), el drenaje biliar preoperatorio (HR 2, 6, i.c. del 95% 1, 3‐6, 2, P = 0.025) y el estado local R1/2 (HR 1, 9, i.c. del 95% 1, 0‐3, 5, P = 0, 043) fueron factores pronósticos independientes de la OS. La recidiva se documentó en 87 (45, 8%) pacientes. El tiempo medio de supervivencia después de la recidiva fue de 16 ± 2 meses. Los factores pronósticos independientes de recidiva fueron la mediana del diámetro del tumor ≥ 5 cm (HR 1, 7, i.c. del 95% 1, 1‐2, 7, P = 0, 020), el tumor de alto grado (G3‐G4) (HR 1, 6, i.c. del 95% 1, 0‐2, 5, P = 0, 034) y el estado local R1 (HR 1, 7, i.c. del 95% 1, 1‐2, 6, P = 0, 020). La resección repetida con intención curativa se realizó en 25 pacientes con iCCA recidivado, con una supervivencia media de 25 meses (i.c. del 95% 16‐34 meses) tras el diagnóstico de recidiva. Los pacientes que se consideraron no resecables después de la recidiva se sometieron a quimioterapia o quimiorradioterapia y presentaron una supervivencia significativamente peor. Conclusión: Los pacientes con recidiva de un iCCA pueden beneficiarse de la resección quirúrgica repetida.